Molecular detection of two virulence factors of Pseudomonas aeruginosa isolated from burn patients - Dakhil Degaim, Zainab; Khamis Al-Malk, Haydar; Methqal Nassar, Alaa; A. Nasir , Ahmed (University of Thi-Qar Journal of Science, 2019)
The present study aimed to identify two virulence genes in P. aeruginosa isolated from infected burn wound. Out of 70 burn swabs, 54 (77%) showed positive growth on enriched media which obtained from burn wound at Al-Mussan Teaching Hospital in Mussan province, Iraq. Only 13 isolates (35%) identified as P. aeruginosa, and those isolates examined using Polymerase Chain Reaction (PCR) for detection the exoS and phzS genes. The results recorded that 46% and 77% of isolates have exoS, phzS genes, respectively. We concluded a P. aeruginosa harbor diverse percentages of both genes as virulence factors, and those factors must be increased the pathogenicity of this pathogen.